2018
DOI: 10.1111/acer.13555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on Alcohol Drinking in Female Mice Selectively Bred for High or Low Alcohol Preference

Abstract: These results show that the temporal parameters of nicotine and alcohol exposure, pattern of alcohol access, and genetic predisposition for alcohol preference influence nicotine's effects on alcohol consumption. These findings in selectively bred mice suggest that humans with a genetic history of alcohol use disorders may be more vulnerable to develop nicotine and alcohol co-use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Rats selectively bred for alcohol preference (alcohol‐preferring [P] rats) self‐administered more nicotine than non‐preferring (NP) rats and exhibited greater nicotine drug seeking 73 . Similarly, nicotine differentially affected alcohol intake in the high‐ and low‐alcohol‐preferring (HAP and LAP, respectively) mice 34 . In Experiment 4, we investigated whether the two replicate HDID lines of mice would differ from their founder line in nicotine intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats selectively bred for alcohol preference (alcohol‐preferring [P] rats) self‐administered more nicotine than non‐preferring (NP) rats and exhibited greater nicotine drug seeking 73 . Similarly, nicotine differentially affected alcohol intake in the high‐ and low‐alcohol‐preferring (HAP and LAP, respectively) mice 34 . In Experiment 4, we investigated whether the two replicate HDID lines of mice would differ from their founder line in nicotine intake.…”
Section: Discussionmentioning
confidence: 99%
“…73 Similarly, nicotine differentially affected alcohol intake in the highand low-alcohol-preferring (HAP and LAP, respectively) mice. 34 In Experiment 4, we investigated whether the two replicate HDID lines of mice would differ from their founder line in nicotine intake. We observed that HDID-2 mice, but not HDID-1 mice, drank more nicotine from the 70 μg/ml solution than the HS/NPT line during both daily 2-h sessions and the final 4-h access period, similar to the effects observed with morphine intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naltrexone has also proven to be efficient in the treatment of pathological gambling [54,55]. A partial nicotine agonist or even nicotine used for nicotine dependence has been used successfully in AUD [56], and methadone (an opioid agonist) has shown efficacy in reducing cocaine abuse among opioid-dependent patients [57]. The theory of addiction as a substance-independent disease is further supported by the perception that people recovering from a given substance commonly tend to change to another substance (e.g., from opiates to cocaine, alcohol, gambling) before successfully recovering from addiction [58].…”
Section: Reward Deficiency Syndrome Index (Rdsi) and Geneticsmentioning
confidence: 99%